Evaluation of physicians’ knowledge of deprescribing, deprescribing tools and assessment of factors affecting deprescribing process. (2023)
Background Polypharmacy is a common global health concern in the older population. Deprescribing has been acknowledged as an important aspect of medication use review that helps to reduce polypharmacy, inappropriate medication uses and medication adverse events, thus ensuring medication optimization and improving health related quality of life. As physicians are primarily responsible for prescribing and monitoring of drug therapy, their perception of deprescribing and knowledge of available deprescribing tools is highly important. This study aimed to explore physicians’ knowledge of deprescribing, deprescribing tools and factors that may affect the deprescribing process. Methods This was a cross-sectional survey carried out among 70 physicians in selected units of a teaching hospital in Nigeria between May and June 2022. Social-demographic information, knowledge of deprescribing and deprescribing tools were obtained using a self-administered, semi-structured questionnaire, while barriers and enablers of medication deprescribing were assessed with modified Revised Patients’ Attitudes Towards Deprescribing (rPATD) Questionnaire. Descriptive and bivariate analyses were carried out using SPSS and α was set at p < 0.05. Results Most of the physicians (56; 80.0%) were aware of the term “deprescribing” and had good knowledge (53;75.7%) of the steps to deprescribing. However, (16; 22.9%) respondents knew of the deprescribing tools, of this, (5;31.3%) were aware of Beers criteria and STOPP/START criteria. Awareness of the term “deprescribing” was significantly associated with knowledge of deprescribing steps (p = 0.012), while knowledge of deprescribing tools was significantly associated with; awareness of the term “deprescribing” (p = 0.029), and daily encounters with older multimorbid patients (p = 0.031). Very important factor affecting physicians deprescribing decisions include benefit of the medication. The most common barrier is lack of information for a full clinical picture of the patient. Conclusion The physicians had good knowledge of the term “deprescribing” and the steps to deprescribing. Specific measures to target the barriers faced by the physicians in deprescribing medications and policies to implement physicians use of existing guidelines to facilitate their deprescribing decisions are essential.